Dialektyka Plotyńska - Przybysławski, Artur (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 1998)
The above text is an attempt to reconstruct Plotinian conception of dialectics (presented in a treatise "On dialectics") based on these parts of "Enneads" which includes Plotinian conception of thinking. Dialectics, according to Plotinus, is not philosopher's instrument as logic is, it is not a method of solving philosophical problems. It is a way which enables soul to return to the One. The return consists of two stages with two corresponding kinds of dialectics; reason dialectics enables soul to know itself through self-thinking and to get to the Intellect whereas dialectics of the Intellect is an exploration of Nous by which getting to the One is possible. Generally dialectics is redeeming thinking raising the soul up to the One, which realizes itself on the level of every lower hypostasis as self-thinking. Dialectics is an embodiment of the Return (epistrofe) – cosmic principle opposite to Outgoing (proodos) – directing everything, what was generated by the One, back to its origin.